Premature Ovarian Failure in a Patient with Robertsonian Translocation Rob (14;15): Is it only a Coincidence? - Sebnem Alanya Tosun; Alptekin Tosun; Enis Ozkaya (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2015)
Women have fixed ovarian follicles after birth and the number of the follicles declines with age.The decrease can be regulated by genetic,hormonal and/or therapy procedures. Radiation exposure can lead to premature ovarian failure (POF). POF is defined as interruption of the ovarian function in an adolescent woman.Genetic disorders including translocations and damage on the ovarian tissue may result POF.The essential diagnostic criteria is an adolescent woman younger than 40 years of age.The diagnosis depends on at least 4 months of amenorrhea and increased FSH levels (≥40 mIU/ml) in 2 blood samples at an interval of 1 month.